Evaluation performance between OFDM and CDMA in perspective of wireless communication - Waheed, Md.; Karim, Lutful; Amin, Faisal (BRAC University, 2010)
This thesis report is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science and Engineering, 2007.